The Burden of OASIS Increases along with Socioeconomic Position – Register-Based Analysis of 980,733 Births in Finland - Räisänen, Sari (Public Library of Science, 2013)
BACKGROUND: Obstetric anal sphincter injury (OASIS) has been identified as a major preventable risk factor for anal incontinence. OBJECTIVE: Aim was to measure national variation in incidence of OASIS by socioeconomic status (SES). METHODS: A retrospective population based case-control study using the data derived from the Finnish Medical Birth Register for the years 1991–2010. A total population of singleton vaginal births was reviewed. We calculated unadjusted incidences of OASIS stratified by SES and vaginal parity, and adjusted risks for OASIS in each social class, after controlling for parity, birthweight, mode of delivery, maternal age and maternal smoking. SES was recorded into five categories based on mother’s occupation at time of birth; upper white-collar workers such as physicians, lower white-collar workers such as nurses, blue-collar workers such as cleaners, others such as students, and cases with missing information. RESULTS: Seven per thousand (6,404 of 980,733) singleton births were affected by OASIS. In nulliparae the incidence of OASIS was 18% higher (adjusted OR 1.18 95% CI 1.04−1.34) for upper white-collar workers and 12% higher (adjusted OR 1.12 95% CI 1.02−1.24) for lower white-collar workers compared with blue-collar workers. Among women in these higher SES groups, 40% of the excess OASIS risk was explained by age, non-smoking, birthweight and mode of delivery. Despite the large effect of SES on OASIS, inclusion of SES in multivariable models caused only small changes in estimated adjusted effects for other established risk factors. CONCLUSIONS: OASIS at the first vaginal delivery demonstrates a strong positive social gradient. Higher SES is associated with a number of risk factors for OASIS, including higher birthweight and non-smoking, but only 40% of the excess incidence is explained by these known risk factors. Further research should address other underlying causes including differences in lifestyle or environmental factors, and inequalities in healthcare provision.